Photo-driven heterogeneous microbial consortium reducing CO2 to hydrocarbons fuel. (1st December 2021) - Xia, Wenjie; Chen, Rui; Li, Yang; Gao, Peike; Li, Chihong; Jin, Tianzhi; Ma, John; Ma, Ting
Abstract: Carbon dioxide as feedstock for hydrocarbon synthesis attracts numerous efforts via the biological or chemical approaches. With the purpose of constructing a robust and highly-efficient platform for CO2 bioconversion to fuel, we investigated a photo-driven bioprocess of directing CO2 reduction to C1 –C6 alkanes/alkenes discovered from the enriched microbial consortia. GC-MS analysis revealed that the maximum yield of total gaseous hydrocarbons was 169.66 μM with the average CO2 reduction rate of 100.87 μM/day decreasing from 11573.39 μM to 5905.73 μM during 50 days culturing. The pathway of CO2 bioconversion was proposed according to the 16S rRNA and metagenomic sequencing that rTCA and Wood-Ljungdahl were mainly contributed to CO2 fixation, and nitrogenase was responsible for the hydrocarbon syntheses. Following these results, a versatile consortium-based platform was developed via the neural network method with the selected Pseudomonas sp., Serratia sp., Candidatus sp., Clostridium sp., Enterococcus sp., Salmonella sp., Rhodospirillum sp., Thalassospira sp., Thioclava sp., Stenotrophomonas sp. and Desulfovibrio sp., which showed the improved CO2 reduction rate of 107.54 μM/day and the higher selectivity of C1 –C4 alkanes than the original consortia. This study demonstrated that this artificially constructed consortium could be a promising platform for converting CO2 to the diverse gaseous alkanes and alkenes. Graphical abstract: Image 1 Highlights: Photo-driven and direct CO2 reduction to hydrocarbons by marine microorganism. Short chain alkanes (C1 –C6 ) and alkenes (C2 –C3 ) were biosynthesized. CO2 reduction rate was 100.87 uM/day. CBB cycle, reductive TCA cycle and Wood-Ljungdahl pathway were responsible for carbon fixation. Nitrogenase played important roles on hydrocarbon synthesis.